Care for pregnant women with anxiety: implications for nursing practice - Ruiz Sánchez, Laura Valentina; Sánchez Alquichire, Ximena Patricia; Ruiz Barajas, Camilo Andrés; Pulido Montes, Maria Andreina; Rincón Romero, Katherine (Salud Integral y Comunitaria, 2026)
Introduction: During the perinatal period, anxiety affects one in five women. These symptoms may worsen in the postpartum stage, increasing the risk of future episodes. It is the responsibility of nursing to address this issue by supporting and collaborating with the new mother to help her overcome anxiety. Specialist nurses in obstetrics and gynecology play a key role in the care of low-risk pregnancy, childbirth, and postpartum.Objective: To characterize nursing care directed at pregnant women with anxiety.Methods: A literature review was conducted using databases such as PubMed, Google Scholar, and ResearchGate with keywords including: pregnancy, anxiety, mental health, nursing, and nursing care. A total of 18 articles were selected, more than 70% of which were published in the last 5 years.Discussion: The most commonly used interventions are counseling, prenatal education, and preparation for childbirth with a companion. Educational interventions have been shown to increase knowledge and promote self-care, which significantly helps reduce anxiety. Humanized nursing care focuses on providing comprehensive support that goes beyond technical and medical aspects, also encompassing the emotional well-being of patients.Conclusions: Anxiety during pregnancy is a frequent and underestimated condition that requires specific attention from the nursing field. In this process, nursing care plays a key role by offering continuous and sensitive support, which directly contributes to maternal-fetal well-being.